EFFECT OF DIFFERENTIATED INSTRUCTION ON ACHIEVEMENT OF LOW MATHEMATICS ACHIEVERS IN PRIMARY SCHOOLS IN ABUJA, NIGERIA - NGOZI, IGBO JANET; SOLOMON, OJONUGWA DOMINIC (Innovare Journal of Education, 2021)
This article examined the effect of two teaching strategies and mathematics achievement on low achievers in Nigeria. Three purposes and three null hypotheses were used. A quasi-experimental research design was used for the study. The sample size for the study consists of 146 (66 males and 80 females) identified low mathematics achievers drawn from six intact classes. The researchers used multi-stage sampling technique. In collecting data, validated Mathematics Achievement Test (MAT) was applied. Internal consistency of the instrument was confirmed. Reliability was determined using Kuder-Rechardson formula 20 (K-R 20) with the estimate of 0.89. The pre-test and post-test data were analyzed and hypotheses tested. Findings of the study revealed that the use of differentiated instruction (DI) in teaching low mathematics achievers in primary school improved the achievement in mathematics more than the control or dictated strategy (F=19.321, P<0.05); the impact of male and on low mathematics achievers was not significant (F= 2.176, P>0.05). The reciprocal action of the teaching methods in relation to male and female low mathematics achievers was not significant (F=1.584, P>0.05). Based on these Findings, differentiated instruction is an effective teaching method for improving the achievement of low mathematics achievers.